2017
DOI: 10.1186/s12879-017-2844-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antimicrobial susceptibility patterns in Staphylococcus aureus strains recovered from patients at two main health facilities in Kabul, Afghanistan

Abstract: Background Staphylococcus aureus (S. aureus) is a major pathogen implicated in skin and soft tissue infections, abscess in deep organs, toxin mediated diseases, respiratory tract infections, urinary tract infections, post-surgical wound infections, meningitis and many other diseases. Irresponsible and over use of antibiotics has led to an increased presence of multidrug resistant organisms and especially methicillin resistant Staphylococcus aureus (MRSA) as a major public health concern in Afghanistan. As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
20
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 24 publications
12
20
4
2
Order By: Relevance
“…This was comparable to the study from Dessie, Ethiopia, 35 but it was lower than the study done in Kabul, Afghanistan (91.4%). 36 Similarly, 60.9% of E. coli was MDR in the present study. This was consistent with the study in Dessie, Ethiopia.…”
Section: Discussionsupporting
confidence: 75%
“…This was comparable to the study from Dessie, Ethiopia, 35 but it was lower than the study done in Kabul, Afghanistan (91.4%). 36 Similarly, 60.9% of E. coli was MDR in the present study. This was consistent with the study in Dessie, Ethiopia.…”
Section: Discussionsupporting
confidence: 75%
“…[32] Naimi et al also found that the resistance pattern to gentamicin was 23% and CZ 22%. [33] Despite, in our study, the frequency of resistance to antibiotics gentamicin, E, cefocytosine, and ceftazidine was 36.23%, 78.26%, 63.04%, and 45.44%, respectively. This can be attributed to the culture of drug use, the pattern of presentation by physicians, the nonproliferation of mutated strains as well as the weather.…”
Section: Discussioncontrasting
confidence: 71%
“…Consistently similar reports from various countries show that around 90% of S. aureus isolated from nosocomial infections and community remain sensitive to Trimethoprim/sulfamethoxazole from the USA (98-100), Europe, Israel, and Turkey (101-103), Japan (104), Canada(105)(106)(107)(108). A study reports higher susceptibility to amoxicillin + clavulanic acid, Doxycycline and Gentamicin, etc (109)…”
mentioning
confidence: 52%